Potential SARS-CoV-2 interactions with proteins involved in trophoblast functions – An in-silico study. (1st January 2021) - Seethy, Ashikh A.; Singh, Sunil; Mukherjee, Indrani; Pethusamy, Karthikeyan; Purkayastha, Kakali; Sharma, Jai Bhagwan; Sharma, Radhey S.; Dhar, Ruby; Karmakar, Subhradip
Abstract: Background: Though a large number of pregnant females have been affected by COVID-19, there is a dearth of information on the effects of SARS-CoV-2 infection on trophoblast function. We explored in silico, the potential interactions between SARS-CoV-2 proteins and proteins involved in the key functions of placenta. Methods: Human proteins interacting with SARS-CoV-2 proteins were identified by Gordon et al. (2020). Genes that are upregulated in trophoblast sub-types and stages were obtained by gene-expression data from NCBI-GEO and by text-mining. Genes altered in pathological states like pre-eclampsia and gestational diabetes mellitus were also identified. Genes crucial in placental functions thus identified were compared to the SARS-CoV-2 interactome for overlaps. Proteins recurring across multiple study scenarios were analyzed using text mining and network analysis for their biological functions. Results: The entry receptors for SARS-CoV-2 – ACE2 and TMPRSS2 are expressed in placenta. Other proteins that interact with SARS-CoV-2 like LOX, Fibulins-2 and 5, NUP98, GDF15, RBX1, CUL3, HMOX1, PLAT, MFGE8, and MRPs are vital in placental functions like trophoblast invasion and migration, syncytium formation, differentiation, and implantation. TLE3, expressed across first trimester placental tissues and cell lines, is involved in formation of placental vasculature, and is important in SARS-CoV (2003) budding and exit from the cells by COPI vesicles. Conclusion: SARS-CoV-2 can potentially interact with proteins having crucial roles in the placental function. Whether these potential interactions identified in silico have effects on trophoblast functions in biological settings needs to be addressed by further in vitro and clinical studies. Graphical abstract: Image 1 Highlights: The effects of the SARS-CoV-2 infection on the functions of placenta remains largely unknown. A large number of human proteins have been found to interact with SARS-CoV-2 proteins. Proteins involved in crucial placental functions were found to be present in the human SARS-CoV-2 interactome. Placenta expresses entry receptors for SARS-CoV-2. It is plausible that SARS-CoV-2 infection can have an impact on diverse and key placental functions.